Syméon stylite le jeune (521-592) : un cas de sainte anorexie ? - Béatrice Caseau (Kentron, 2003)
Symeon the Younger became a stylite not far from Antioch when he was seven years old. His ascetical fasting far exceeded the fasting practiced by the other monks in his monastery. He only partook of the eucharist. Although rebuked by the hegoumenos for refusing to eat, Symeon maintained his pratice and even theorized about the spiritual benefits one could draw from extreme fasting. Was Symeon an anorectic? That is the question adressed in this article.